Examination of the Effect of High School Students Physical Activity Levels on Their Problem Solving Skills - Nimet Korkmaz (Sport Mont, 2017)
The purpose of this study is to be knowledgeable with demographic characteristics, Body mass index, physical activity levels, problem solving skills and sub-dimensions of the students receiving education at Anatolia High Schools and examine the effect of the physical activity levels of these students on their problem solving skills. The population of the study was included a total of 451 students (female=264; male=187) receiving education at the Anatolia High Schools in the Osmangazi district. In this study, the data was collected via the “International Physical Activity Questionnaire-Short Form” and the “Problem Solving Skill Scale” (PSS). It was determined that the males’ physical activity values (3822.85 MET- min./week), were higher compared to those of the females (2103.17). On the contrary, the problem solving skills of the males (mean 2.91) were lower than those of the females (mean 2.95). The SPSS 23.0 for Windows program was used in the statistical analyses of the data. In order to see if the data distributed normally or not, Tabachnick and Fidell coefficients were used for the kurtosis and skewness values. For the comparison of the problem solving skills scores and the physical activity scores, the t test statistical method was used. In conclusion, no significant relationship at p<0.05 level was determined between the students’ problem solving skills and their physical activity states.